The effects of audit client tenure, audit lag, opinion shopping, liquidity ratio, and leverage to the going concern audit opinion - Rahmat Akbar Simamora; Hendarjatno Hendarjatno (Asian Journal of Accounting Research, 2019)
The going concern audit opinion is an audit opinion issued by an auditor to evaluate the company’s ability in maintaining the business continuity. The purpose of this paper is to discover the effects of audit client tenure, audit lag, opinion shopping, liquidity ratio and leverage on the going concern audit opinion.The study used secondary data obtained from financial reports and independent audit reports published by Indonesian Stock Exchange (ISE) as well as Indonesian Capital Market Directory. Besides, the population of the study included manufacturing companies registered in ISE from 2009 to 2013. Further, the present study applied purposive sampling technique which resulted in 16 companies used as the sample of the study. Then the hypothesis was examined by applying logistic regression.Results of the hypothesis examination indicated that the variables of opinion shopping and leverage affected the going concern audit opinion, whereas the variables of audit client tenure, audit lag and liquidity ratio did not affect the going concern audit opinion.Results of the hypothesis examination indicated that the variables of opinion shopping and leverage affected the going concern audit opinion, whereas the variables of audit client tenure, audit lag and liquidity ratio did not affect the going concern audit opinion.